2020
DOI: 10.21608/ejmm.2020.249865
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Fosfomycin against Extended-Spectrum-Beta-Lactamase producing Enterobacteriaceae isolates from Menoufia University Hospitals

Abstract: Background: Fosfomycin is an old antibiotic that is being reconsidered for the treatment of lower urinary tract, due to the global increasing resistance of several bacteria to numerous-antimicrobials. Objectives: To evaluate the activity of fosfomycin and to detect fosfomycin resistant genes (FosA3 and FosC2) in extended-spectrum-beta-lactamase producing Enterobacteriaceae isolates from Menoufia University Hospitals. Methodology: The study included 155 samples collected from patients from different departments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In this study 180 Gram negative bacilli were isolated from 310 collected urine samples representing 58%. Similar was reported by Gharieb et al, 23 in Egypt found that out of 155 studied patients, 99 (64%, n= 99) isolates were Gram negative bacilli. Several studies reported more than 50 % of their CAUTI were caused by Gram negative organisms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this study 180 Gram negative bacilli were isolated from 310 collected urine samples representing 58%. Similar was reported by Gharieb et al, 23 in Egypt found that out of 155 studied patients, 99 (64%, n= 99) isolates were Gram negative bacilli. Several studies reported more than 50 % of their CAUTI were caused by Gram negative organisms.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, (86.7%, n= 156) strains were MDR, and most of them (60.9%, n=95) were isolated from ICU, and (39.7%, n=62) of them were E. coli which represents (82,7%, n=62) of all E. coli isolates. Gharieb et al, 23 11 in Iran. The difference in the rate of resistance to fosfomycin may be due to the amount of antibiotic usage in the different area.…”
Section: Discussionmentioning
confidence: 99%